EP393/#809 Validation of a frailty index in gynaecologic oncology. (4th December 2022) - Woo, Lawrence; Mateshaytis, Jennifer; Mal, Hanan; Ghatage, Prafull; Cameron, Anna
Abstract : Objectives: Frailty is associated with adverse outcomes in the oncologic and surgical patient. Frailty indices have been developed in multiple surgical fields and have been found to be predictive of post-operative morbidity and mortality. We aim to validate the Modified Frailty Index amongst our patient population. We hypothesize that those with increased frailty are at increased risk of surgical morbidity and mortality and that identifying these patients and applying Quality Improvement (QI) designed interventions may reduce adverse outcomes. Methods: New patients who presented to the Gynaecologic Oncology service in Calgary, Alberta completed a frailty index. Between January 2020 and May 2021, frailty indices were collected on 616 patients, of which 475 underwent surgery. Frailty scores were compared to the primary outcome measures including: length-of-stay, 30-day morbidity, re-admission, and mortality. Thirty-day morbidity was assessed with the Clavien-Dindo classification. Secondary outcome measures include: documented residual disease, consultations within hospital, and non-home discharge. Data regarding patients' baseline characteristics, malignancy, and surgery were also documented. Results: Baseline analysis show frail patients are more likely to experience post-surgical complications and to have a longer length-of-stay (p = 0.018 for both). There is a trend towards an increased frequency of readmissions (p = 0.052). Sub-group analysis reveal a higher grade of complications based on Clavien-Dindo classification for frail endometrial cancer patients (p = 0.022). Conclusions: Preliminary analysis reveal the Modified Frailty Index is predictive of increased risk of post-surgical morbidity and complications in our population. Further application of the index and interventions may assist in surgical decision-making and improving post-operative outcomes.